2016
DOI: 10.4238/gmr.15028007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interleukin 19 serum levels and single nucleotide polymorphisms in systemic lupus erythematosus

Abstract: ABSTRACT. Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disease that affects multiple organs and diminishes a patients' quality of life. It has been suggested that interleukin 19 (IL-19) is engaged in intercellular signal transduction, which is related to the immune response and the local inflammatory reaction. Single nucleotide polymorphisms (SNPs) have been used to explore the genetic basis underlying the pathogenesis of SLE. In this study, we investigated the potential correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“… 23 Recent studies have shown that HIF-1α and IL-19 are associated with many chronic inflammatory diseases. 8 , 9 , 12 15 , 23 We tested the serum levels of HIF-1α and IL-19 in stable COPD patients and tried to disclose their biological significance in the occurrence and development of COPD. We found that patients with stable COPD showed a higher expression of serum HIF-1α compared with the control group (healthy elderly) and upregulation of serum HIF-1α was positively correlated with the GOLD grade, mMRC score, and medical history of patients, which means that the serum level of HIF-1α is related to the disease progression of stable COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 Recent studies have shown that HIF-1α and IL-19 are associated with many chronic inflammatory diseases. 8 , 9 , 12 15 , 23 We tested the serum levels of HIF-1α and IL-19 in stable COPD patients and tried to disclose their biological significance in the occurrence and development of COPD. We found that patients with stable COPD showed a higher expression of serum HIF-1α compared with the control group (healthy elderly) and upregulation of serum HIF-1α was positively correlated with the GOLD grade, mMRC score, and medical history of patients, which means that the serum level of HIF-1α is related to the disease progression of stable COPD.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Hypoxia can induce continuous expression of HIF-1α and promote pulmonary vascular remodeling and aggravate the course of COPD. 10 , 11 IL-19 can be detected in human monocytes, 12 and the expression of IL-19 can be enhanced by stimulating B and T lymphocytes. 13 Studies show that increased IL-19 is involved in the incidence of autoimmune diseases 12 such as psoriasis, asthma, and rheumatoid arthritis by upregulating pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Recent findings showed that serum levels of IL-19 were significantly related to clinical characteristics in SLE patients and gene polymorphisms of IL-19 indicated a susceptibility to SLE risk. 15,16 Protein expression of IL-20 was upregulated in mesangial cells from SLE-prone, NZB/W mice, and human IL-20 protein in both mesangial cells and inflammatory cells in kidney biopsies of patients with lupus nephritis was elevated. 17 Mesangial cells treated with IL-20 upregulated the transcripts of CCL2, CCL5, CXCL10 and IL-6, which are involved in the pathogenesis of lupus nephritis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, abnormal expression levels of B cell lymphoma-2 (Bcl-2) and interleukin-19 (IL-19) were closely related to disease pathogenesis in Chinese patients. 3 – 5…”
Section: Introductionmentioning
confidence: 99%